Evolving Social Media Strategies in Local Journalism: experiences from Argentine Patagonia - Rost, Alejandro (2024)
Studies on journalistic work and production on social media typically focus on large media outlets in developed countries. In this article, we shift the lens to a peripheral area of a peripheral country: Argentine Patagonia. Our objective was to analyse journalistic production on Instagram, Facebook, and Twitter in the eight most-followed local and regional news media outlets. We analysed the narratives, the extent to which they apply transmedia journalism, and how they have evolved compared to studies from 2021. We also conducted structured interviews with social media managers to gain insight into their professional practices. We conclude that, 15 years since the creation of the first profiles, promoting website content remains the primary goal of North Patagonian media networks. Since 2021, there have been more frequent updates but less native production, especially on Facebook and Twitter. Despite the shortage of staff and precarious working conditions, some news media outlets have been able to innovate on Instagram, introducing a variety of multimedia formats, a more conversational tone, diverse update rhythms, adapted content, and even specific content that is organised into sections. Information production for the platforms has been integrated into journalistic routines even when public interaction with the audience remains very limited.